Penerapan Project Based Learning Sebagai Upaya dalam Mengatasi Krisis Pembelajaran (Learning Loss) pada Mata Pelajaran Ekonomi Kelas XI di SMA Negeri 16 Bekasi Tahun Ajaran 2025/2026 - Siti Rohimah; Agus Wibowo; Aditya Pratama (Jurnal Ilmiah Literasi Indonesia, 2025)
This study aims to identify, describe, and analyze the implementation of Project Based Learning (PjBL) as an effort to overcome learning loss in Economics for 11th-grade students at SMA Negeri 16 Bekasi during the 2025/2026 academic year. Furthermore, this research also aims to describe the supporting and inhibiting factors in the implementation of PjBL. The research results indicate that the implementation of PjBL at SMA Negeri 16 Bekasi is structured, starting from thorough planning (coordination meetings, team formation, module development) to student-centered implementation. PjBL proved effective in increasing active student engagement, learning motivation, critical thinking skills, and collaboration, as well as helping students apply economic theories in real-world contexts. This significantly minimized the occurrence of learning loss. Key supporting factors include the support of the Merdeka curriculum, the school's commitment, the active role of teachers, student enthusiasm, collaboration, and tangible project outcomes. However, there were also inhibiting factors such as time constraints, differences of opinion within student groups, limited facilities and infrastructure, and a lack of coordination among students.